Effects of Eutrophication and Different Water Levels on Overwintering of Eichhornia crassipes at the Northern Margin of Its Distribution in China - Yu, Haihao; Dong, Xianru; Yu, Dan; Liu, Chunhua; Fan, Shufeng (Frontiers in Plant Science, 2019)
When exotic species are introduced into new areas, establishment is a vital step in their invasion process. Therefore, overwintering strategies determine whether an exotic species from low latitudes can successfully invade middle- and high- latitude areas. In this study, we investigated the effects of nutrient and water drawdown on overwintering in an exotic aquatic plant from the tropical zone, Eichhornia crassipes, at the northern margin of its distribution in China. The population density, size of individuals, and the size and nitrogen concentration of overwintering organs (stem base) of E. crassipes that grew in high nutrition water were greater than those grew in low-nutrient water before winter. The overwinter survival rate of E. crassipes was significantly affected by the water level and nutrient. The thick and dense floating mat of E. crassipes can increase the temperature of water bodies, therefore, the overwinter survival rate of E. crassipes was higher in constant-water-level and high-nutrient treatment. In contrast, due to the loss of heat preservation provided by the floating mats and the low nitrogen concentration in the stem base, all individuals of E. crassipes died in constant-water-level and low-nutrient treatment. In the water-drawdown treatments, the stem base of E. crassipes was directly exposed to low-temperature air; therefore, the overwinter survival rate of E. crassipes was lower. Our results reveal that eutrophication can not only improve the competitiveness of E. crassipes, but can also improve the survival rate of overwintering plants in temperate regions. Our study also suggests that removing nutrients from the water and regulating the water level can limit the invasion of E. crassipes in temperate and subtropical regions.